A novel compound heterozygous mutation of the SMARCAL1 gene leading to mild Schimke immune-osseous dysplasia: a case report - Shuaimei Liu; Mingchao Zhang; Mengxia Ni; Peiran Zhu; Xinyi Xia (BMC, 2017)
Abstract Background Schimke immune-osseous dysplasia (SIOD, OMIM 242900) is characterized by spondyloepiphyseal dysplasia, T-cell deficiency, renal dysfunction and special facial features. SMARCAL1 gene mutations are determined in approximately 50% of patients diagnosed with SIOD. Case presentation The case presented here is that of a 6-year-old boy who was born at 33 weeks to healthy, non-consanguineous Chinese parents. He presented with short stature (95 cm; <3rd percentile) and proteinuria. Initially suspected of having IgM nephropathy, the patient was finally diagnosed with mild Schimke immune-osseous dysplasia. One novel mutation (p.R817H) and one well-known mutation (p.R645C) was identified in the SMARCAL1 gene. Conclusion This report describes a clinical and genetic diagnostic model of mild SIOD. It also highlights the importance of molecular testing or clinical diagnosis and the guidance it provides in disease prognosis.